Development of Pineapple cv. Turiaçu with Aerobic Biofertilizer Applications in Planting with and without Mulching - Santos, José Osman Silvino; Souza, Joilma Maria de; Santos, Giulia da Costa Rodrigues dos; Vaz, André Felipe de Sousa; Antunes, Luiz Fernando de Sousa; Martelleto, Luiz Aurélio Peres (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
The pineapple crop (Ananas comosus) is of socio-economic importance in Maranhão, with the regional cultivar 'Turiaçu' standing out for its sensory qualities. However, local productivity is lower than the national average and the lack of studies on sustainable management limits its potential. The aim of this study was to evaluate the development, productivity and fruit quality of the 'Turiaçu' pineapple under application of aerobic biofertilizer (BA), compared to mineral fertilizer, and to analyze the effect of different soil covers (plastic mulch and burlap). The experiment was conducted in a randomized block design (RBL), with 8 treatments and 4 replications, totalling 576 plants. The treatments included combinations of BA (applied every 14 days), plastic mulch, leaf litter, synthetic fertilizer (control) and an untreated control. Vegetative (fresh and dry mass, length and width of leaf D), productive (fruit mass and size, basal and apical diameter, natural flowering, toppling) and quality (soluble solids, incidence of fusarium and fruit grading) characteristics were evaluated. Mulch as a soil cover promoted greater growth of the 'Turiaçu' cultivar. In contrast, chemical fertilization proved ineffective and plastic mulching caused plant instability. Although the use of BA did not outperform burlap in terms of productivity, it showed potential when associated with organic practices. It can be concluded that litter is a promising alternative for managing the 'Turiaçu' pineapple, favoring the development and sustainability of production.